Prediksi Self Efficacy Dan Personality Traits Terhadap Entrepreneurial Intentions Di Kalangan Mahasiswa - Yeremia Yeremia; Hannes Widjaja (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2019)
This study was conducted to determine the relationship of self-efficacy and personality traits to entrepreneurial intentions of Tarumanagara University Faculty of Communication Science students. The sampling menthod is done by purposive sampling method. Data collection was done by distributing questionnaires to 100 respondents. The data analysis technique uses the structural least partial (PLS) model. The results of this study are that there is no significant positive relationship between self-efficacy, conscientiousness, and extraversion with Tarumanagara University Faculty of Communication students entrepreneurial intentions, there is no negative relationship significant between neuroticism and entrepreneurial intentions of Tarumanagara University Faculty of Communication Sciences students. In addition, there is a significant positive relationship between openness to experience and agreeableness with entrepreneurial intentions of Tarumanagara University Faculty of Communication students studentsPenelitian ini dilakukan untuk mengetahui hubungan self-efficacy dan personality traits terhadap entrepreneurial intentions mahasiswa Fakultas Ilmu Komunikasi Universitas Tarumanagara. Metode pengambilan sampel dilakukan dengan metode purposive sampling. Pengumpulan data dilakukan dengan membagikan kuesioner ke 100 responden. Teknik analisis data menggunakan teknik structural equation model partial least square (PLS). Hasil dari penelitian ini adalah tidak terdapat hubungan positif yang signifikan antara self-efficacy, conscientiousness dan extraversion dengan entrepreneurial intentions mahasiswa Fakultas Ilmu Komunikasi Universitas Tarumanagara, tidak terdapat hubungan negatif yang signifikan antara neuroticism dengan entrepreneurial intentions mahasiswa Fakultas Ilmu Komunikasi Universitas Tarumanagara. Selain itu terdapat hubungan positif yang signifikan antara openness to experience dan agreeableness dengan entrepreneurial intentions mahasiswa Fakultas Ilmu Komunikasi Universitas Tarumanagara.